2009
DOI: 10.1016/j.biomaterials.2009.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Engineering retinal progenitor cell and scrollable poly(glycerol-sebacate) composites for expansion and subretinal transplantation

Abstract: Retinal degenerations cause permanent visual loss and affect millions world-wide. Presently, a novel treatment highlights the potential of using biodegradable polymer scaffolds to induce differentiation and deliver retinal progenitor cells for cell replacement therapy. In this study, we engineered and analyzed a micro-fabricated polymer, poly(glycerol sebacate) (PGS) scaffold, whose useful properties include biocompatibility, elasticity, porosity, and a microtopology conducive to mouse retinal progenitor cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 36 publications
1
124
0
1
Order By: Relevance
“…To date, biodegradable synthetic thermoset elastomer PGS has been widely explored for various tissue engineering applications [6,8,[20][21][22][23][24][25][26][27][28][29][30]. PGS exhibits faster degradation rate of 17% in 9 weeks in PBS, elastic modulus of around 0.282 MPa, and it's tensile strength is above 0.5…”
Section: Effect Of Polymer Concentrationmentioning
confidence: 99%
“…To date, biodegradable synthetic thermoset elastomer PGS has been widely explored for various tissue engineering applications [6,8,[20][21][22][23][24][25][26][27][28][29][30]. PGS exhibits faster degradation rate of 17% in 9 weeks in PBS, elastic modulus of around 0.282 MPa, and it's tensile strength is above 0.5…”
Section: Effect Of Polymer Concentrationmentioning
confidence: 99%
“…Collagen-functionalized nanofibers improved cell adhesion and migration compared to non-functionalized nanofibers [69]. Polymer scaffolds made from PLGA [1,46], PMMA [49] and PGS [52,54] required protein modification of the surface with either laminin or a combination of laminin and poly-L-lysine to achieve RPC attachment. Additionally, PLLA/PLGA scaffolds needed a concentrated cell solution in order to achieve appropriate levels of cell attachment [46].…”
Section: Surface Chemistrymentioning
confidence: 99%
“…By using PGS scaffolds as a cell delivery vehicle, 13% and 7% of grafted cells migrated into the C57BL/6 and Rho-/-mouse retinal explants at one week. 1.5% and 0.8% of grafted cells migrated into the C57BL/6 and Rho-/-mouse retina four weeks post-transplantation [54].…”
Section: Pgsmentioning
confidence: 99%
“…One of the most promising therapies for late-stage retinal degeneration is to deliver retinal stem or progenitor cells to the subretina. 3,4 Several studies indicate that a typical bolus injection of mouse retinal progenitor cells (mRPCs) leads to massive new cell loss through efflux and death. 3,5 Recently it was demonstrated that a tissue engineering approach, the usage of a biocompatible polymer scaffold, improved the mRPCs survival and promoted the integration of transplanted mRPCs in host retinal tissue following transplantation.…”
Section: Introductionmentioning
confidence: 99%